Development of an Augmented Reality Assisted Science Game Card to Enhance Students’ Learning Motivation on the Topic of Classification of Living Things - Lidya Nainggolan; Khairiza Lubis; Masdiana Sinambela; Martina Asiati Napitupulu; Aswarina Nasution (Fakultas Tarbiyah dan Ilmu Keguruan UIN Sultan Aji Muhammad Idris Samarinda, 2026)
This study aimed to determine the feasibility, practicality, and effectiveness of an Augmented Reality-assisted Science Game Card in enhancing students’ learning motivation on the topic of classification of living things. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The product was validated by material, design, learning, and instrument experts before being implemented with 10 students in a small-scale trial and 31 seventh-grade students in a large-scale trial. Data were collected through validation sheets, response questionnaires, learning motivation questionnaires, and observation sheets. The results showed that the developed media was feasible, obtaining validation scores of 79.5% (Valid), 90.0% (Highly Valid), 90.8% (Highly Valid), and 94.0% (Highly Valid). The media was also highly practical, with teacher and student response scores of 100%, 84.5%, and 97.4%, respectively. Furthermore, the effectiveness test indicated a significant improvement in students’ learning motivation, with a Wilcoxon significance value of 0.000, an N-Gain score of 0.701 (High), and a motivation observation score of 86.29% (Highly Motivated). Therefore, the Augmented Reality-assisted Science Game Card is feasible, practical, and effective for enhancing students’ learning motivation.